Big Data in Social Media: Introduction, Methodology, Applications - Akash K Salian (International Journal of Advanced Research in Science, Communication and Technology, 2024)
In this paper, we have discussed about how Big-Data has influenced the working, modeling and behavior of social media on a huge scale. Not only use but also storing and restructuring of data have created a new model and pattern of data on its own. Big-data is used and managed in a lot many ways by the different social media applications and platforms according to the need and methodology accepted. We also saw how we can use this available data can help us to grow our business